Perancangan Sistem Informasi Monitoring Keluhan Sasaran Vaksinasi COVID-19 Bagi Masyarakat Umum Berbasis Web ( Studi Kasus : Dinas Kesehatan Kota Bandung) - Reihan Fazri Aldiansyah; Syams Syair Ramadhan; Jaenal Arifin; Cahyadi Agustin (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
Bandung Health Office as a Health Agency that always provides quality services is currently focused on handling pandemics, especially in the implementation of vaccination programs as a strategy to combat the COVID-19 outbreak. Therefore, monitoring of complaints experienced by the community after vaccination is required. The problem experienced today is the unavailability of containers to accommodate and manage data on COVID-19 vaccination complaints using the information system. The purpose of this research is to design a website-based information system that supports the process of monitoring and handling COVID-19 vaccination complaints in the Bandung Health Office by presenting informative and transparent data so as to facilitate the public in reporting and obtaining complaint information easily. The system development method uses waterfall model, while the system functional design method uses object-oriented modeling approach with Unified Modelling Language (UML). Black box test results obtained a 100 percentage of system functionality success. Evaluation test results with System Usability Scale (SUS) questionnaire obtained the final test score of 77.6 with Acceptable category and B Grade Scale. So based on the test results, the system can run easily according to the needs of the user. This research resulted in a web-based information system that makes it easier for health workers to efficiently manage COVID-19 vaccination complaint reporting data.